2018
DOI: 10.1002/14651858.cd011654.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Fly control to prevent diarrhoea in children

Abstract: BackgroundDiarrhoeal disease accounts for millions of child deaths every year. Although the role of flies as vectors of infectious diarrhoea has been established, fly control is not often mentioned as an approach to decrease childhood diarrhoea. Theoretically, fly control for decreasing diarrhoea incidence can be achieved by intervening at four different levels: reduction or elimination of fly breeding sites; reduction of sources that attract houseflies; prevention of contact between flies and disease‐causing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
1
11
0
1
Order By: Relevance
“…2 Continued diarrhea can cause loss of fluid and electrolytes, and may even become life-threatening, especially in children and adults who are immunosuppressed or malnourished. 3 Although not life-threatening for adults, diarrhea still has a high incidence. 1 Diarrhea usually has intestinal tract noninfectious symptoms that could be caused by improper diet and malnutrition, and infectious symptoms that are usually caused by a variety of bacterial, viral, and parasitic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…2 Continued diarrhea can cause loss of fluid and electrolytes, and may even become life-threatening, especially in children and adults who are immunosuppressed or malnourished. 3 Although not life-threatening for adults, diarrhea still has a high incidence. 1 Diarrhea usually has intestinal tract noninfectious symptoms that could be caused by improper diet and malnutrition, and infectious symptoms that are usually caused by a variety of bacterial, viral, and parasitic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these deaths occur in South Asia and sub-Saharan Africa [1], and in low-income countries [2]. Thus, controlling diarrhea is essential if the world desires to achieve sustainable development goals for child health [3]. In Indonesia, diarrhea affects 11% of children under 5 and is the second-largest cause of death [4].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of housefly control as prevention for infectious diarrhea in community settings has long been questioned. Vector control can be accomplished by reducing or eliminating breeding sites, reducing housefly attraction sources, and preventing interaction between flies and food, food utensils, people, or disease-causing organisms [3], [6], [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…The house fly, Musca domestica L. , is known to carry pathogens including bacteria, viruses, fungi, and parasites which cause life threatening diseases in humans and animals [ 5 , 6 ]. Houseflies breed in human feces [ 7 ] and the existing studies [ 8 , 9 , 10 , 11 , 12 ] have shown increased incidences of diarrhea during the periods of high fly density. Most importantly, several existing studies [ 8 , 13 , 14 , 15 ] have shown that a reduction in housefly density may affect the reduction in diarrhea incidence as well.…”
Section: Introductionmentioning
confidence: 99%